The Real Effects of Lending Relationships on Innovative Firms and Inventor Mobility - Hombert, Johan; Matray, Adrien (Review of Financial Studies, 2017)
We study how relationship lending determines the financing of innovation. Exploiting a negative shock to relationships, we show that it reduces the number of innovative firms, especially those that depend more on relationship lending such as small, opaque firms. This credit supply shock leads to reallocation of inventors whereby young and productive inventors leave small firms and move out of geographical areas where lending relationships are hurt. Overall, our results show that credit markets affect both the level of innovation activity and the distribution of innovative human capital across the economy.